Trustee Related Determinants of Scheme Design in Occupational Defined Contribution Schemes in Kenya - Tari, Justus; Wawire, Nelson H.W.; Ombuki, Charles (Research Journal of Finance and Accounting, 2015)
This paper aims to provide an understanding of trustee related determinants of scheme design in occupational defined contribution schemes (ODCS) in Kenya. ODCS involve no promises about the size of the benefits and no risk to the employer. The risk of ending up with low or no benefits falls entirely on the scheme members. It is necessary therefore, that determinants of scheme design are carefully considered in establishment and review of defined contribution schemes to deliver adequate benefits to members. Based on modern portfolio and the life cycle theories, the study investigated the key trustee related determinants of scheme design in ODCS in Kenya. Primary data were collected using a questionnaire administered to scheme administrators in the sample.Descriptive statistics were used to profile respondents, describe sample characteristics and a logistic econometric model was applied to evaluate the trustee related determinants of scheme design. The study showed that the key trustee related determinant of scheme design was investment strategy. From the findings, it was recommended that trustees should in addition consider investment returns, target pension, charges by service providers and annuity rates in designing schemes. This would guarantee members a reasonable standard of living after retirement.
Keywords: Scheme Design; Occupational Defined Contribution Schemes; Trustees